Radiochromic film based dosimetry of image‐guidance procedures on different radiotherapy modalities. (8th November 2014) - Nobah, Ahmad; Aldelaijan, Saad; Devic, Slobodan; Tomic, Nada; Seuntjens, Jan; Al‐Shabanah, Mohammad; Moftah, Belal
Abstract : In this work we compare doses from imaging procedures performed on today's state‐of‐the‐art integrated imaging systems using a reference radiochromic film dosimetry system. Skin dose and dose profile measurements from different imaging systems were performed using radiochromic films at different anatomical sites on a humanoid RANDO phantom. EBT3 film was used to measure imaging doses from a TomoTherapy MVCT system, while XRQA2 film was used for dose measurements from kilovoltage imaging systems (CBCT on 21eX and TrueBeam Varian linear accelerators and CyberKnife stereoscopic orthogonal imagers). Maximum measured imaging doses in cGy at head, thorax, and pelvis regions were respectively 0.50, 1.01, and 4.91 for CBCT on 21eX, 0.38, 0.84, and 3.15 for CBCT on TrueBeam, 4.33, 3.86, and 6.50 for CyberKnife imagers, and 3.84, 1.90, and 2.09 for TomoTherapy MVCT. In addition, we have shown how an improved calibration system of XRQA2 film can achieve dose uncertainty level of better than 2% for doses above 0.25 cGy. In addition to simulation‐based studies in literature, this study provides the radiation oncology team with data necessary to aid in their decision about imaging frequency for image‐guided radiation therapy protocols. PACS number: 87.53.Bn, 87.55.Qr, 87.56.Fc